2019
DOI: 10.1186/s12888-019-2016-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between childhood maltreatment and adult depression: a mediation analysis

Abstract: BackgroundThere is ample evidence showing that childhood maltreatment (CM) is a risk factor for the development of depression in adulthood. However, little is known about the psychological processes mediating this relationship. This study used a large community sample to investigate the mediating role of emotional, cognitive and/or interpersonal dysfunctions on the one hand and posttraumatic stress disorder symptoms on the other hand.MethodsOne thousand twenty seven participants of a community sample filled ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 59 publications
9
25
0
6
Order By: Relevance
“…Specially, the present study is the first to demonstrate that childhood maltreatment is positively correlated with hubristic pride and negatively correlated with authentic pride. This confirms the view of learned helpless theory that adverse experiences would impact individuals' causal attribution and influence the emotional responses to events 24,25 . Second, to some extent, these findings extend research on pride and envy in the context of Chinese culture.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Specially, the present study is the first to demonstrate that childhood maltreatment is positively correlated with hubristic pride and negatively correlated with authentic pride. This confirms the view of learned helpless theory that adverse experiences would impact individuals' causal attribution and influence the emotional responses to events 24,25 . Second, to some extent, these findings extend research on pride and envy in the context of Chinese culture.…”
Section: Discussionsupporting
confidence: 81%
“…This confirms the view of learned helpless theory that adverse experiences would impact individuals' causal attribution and influence the emotional responses to events. 24,25 Second, to some extent, these findings extend research on pride and envy in the context of Chinese culture. Previous studies have mostly explored the effect of pride on envy from the perspective of interpersonal interaction.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 61%
See 2 more Smart Citations
“…Many studies have demonstrated that experiencing abuse and neglect during childhood increases the likelihood of developing mental disorders in adult life. [16][17][18][19][20][21] Yet, few studies have investigated possible psychological mediators between child maltreatment and mental disorders, 22,23 especially those that could mitigate the negative effects of early experiences of abuse and neglect. 24 Metel et al 22 found that resilience and cognitive biases partially mediate the relationship between early exposure to traumatic life events and depressive symptoms, and recent studies have demonstrated that social support mediates the effect of childhood maltreatment on mental health, [24][25][26][27] but, as far as we know, no studies have investigated LS as a mediator in the relation between childhood maltreatment and mental disorders.…”
Section: Introductionmentioning
confidence: 99%